ANALISIS IMPLEMENTASI PEMBANGUNAN BERKELANJUTAN DI JAWA TIMUR - Pratiwi, Niken; Santosa, Dwi Budi; Ashar, Khusnul (EP FEB UNS, 2018)
Sustainable development is a multidimensional development paradigm that considers the interests of future generations in addition to meeting current needs. The linkages between economic, social and environmental aspects are manifested in a measure of fairness, comfort and sustainability. This study aims to analyze the implementation of sustainable development in East Java based on economic, social and environmental variables and know the most influential factors on the success of sustainable development using quadrant analysis based on Klassen Tipology and cluster analysis. The result of the research shows the formation of three cluster areas in East Java that are categorized into advanced regions, potential areas and disadvantaged areas. In general, development in East Java has led to sustainable development characterized by the development of economic development, increased social welfare and reduced social problems, and improved environmental conditions during the year 2011 to 2015. Research shows that the imbalance between regions that are identical to the sense of justice is the most decisive factor in the implementation of sustainable development in East Java Keywords: Sustainable Development, Klassen Tipology, cluster analysisJEL Classification:P28, R5